3D Millimeterwellen-Abbildung von dielektrischen Probek?rpern und numerische Rekonstruktion der Materialeigenschaften - Gumbmann, Frank; Weinzierl, Jochen; Tran, Hue Phat; Schmidt, Lorenz-Peter (DGZfP-Jahrestagung Mai, 2007)
UnivIS-Import:2015-04-16:Pub.2007.tech.IE.LEH.3dmill

3D SAR Processing for a Fast Scanning Millimeter-Wave Short Range Imaging System - Gumbmann, Frank; Tran, Hue Phat; Weinzierl, Jochen; Schmidt, Lorenz-Peter (European Conference on Synthetic Aperture Radar (EuSAR 08,03.-05.06.08), 2008)
A fast scanning short range radar imaging system for security or non-destructive testing applications is presented. The goal was to develop an 3D-imaging system with range independent lateral resolution down to 3 mm and a range resolution down to 6 mm. Therefore a setup with non focusing antennas and a broadband (75-100 GHz) SFCW (stepped frequency continuous wave) radar module were developed. A reconstruction of the device under test (DUT) with high lateral resolution is derived by applying numerical techniques based on the synthetic aperture radar (SAR) principle. To collect as many pixels as possible over a two dimensional aperture a rotating virtual antenna was developed. It is realized by a Gaussian beam transformation of the feed antenna beam waist onto a subreflector. By rotating the quasioptical transformator, an elliptical mirror, the transformed virtual antenna is rotated as well. This scanner concept is applied to planar and cylindrical geometries.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.3dsarp

A 300 GHz quasioptical schottky frequency doubler - Shalaan, M; Bozzi, M; Weinzierl, Jochen; Beilenhoff, K; Conciauro, G; Brand, Hans; Hartnagel, H (International Journal of Infrared and Millimeter Waves, 1997)
A monolithically integrated frequency multiplier based on a planar antenna providing impedance matching has been realized and measured at 300 GHz. Each of the two circuits comprises a Schottky varactor, slot antenna, MIM-capacitor and microstrip bias feed. The theoretical design aspects, the technological approach and the RF performance are addresse
lhft_intern.bib::thirty_years_LHFT_413

Advanced Broadband Millimetre-Wave Characterization Techniques of Dielectrics - Gumbmann, Frank; Tran, Hue Phat; Weinzierl, Jochen; Schmidt, Lorenz-Peter (9th European Conference on Nondestructive Testing, Berlin, September, 2006)
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.LEH.advanc

A Fast Scanning W-Band System for Advanced Millimetre-Wave Short Range Imaging Applications - Tran, Hue Phat; Gumbmann, Frank; Weinzierl, Jochen; Schmidt, Lorenz-Peter (IEEE National Radar Conference - Proceedings, 2006)
The paper presents the development of a fast scanning W-Band (75-100 GHz) system and a suitable antenna concept for advanced imaging applications. The goal is to obtain a broadband frequency response from a large target area within a short time period. Two typical approaches for the design of a free space millimetre-wave imaging setup will be discussed. The first approach consists of a focused bistatic measurement setup that includes a combination of a conical horn and a dielectric lens in order to focus the beam. The basic idea of the second approach is to use an unfocused measurement setup employing synthetic aperture radar (SAR) algorithms in order to focus the image numerically. Both measurement setups will be discussed with respect to the capability for fast scanning mm-wave imaging systems. Experimental results on planar test objects demonstrate the performance of the developed W-Band system compared to a commercial vector network analyzer (VN

A fast scanning W-band system for advanced millimetre-wave short range imaging applications - Weinzierl, Jochen; Schmidt, Lorenz-Peter; et al. (3rd European Radar Conference, EuRAD 2006, 2007)
The paper presents the development of a fast scanning W-Band (75-100 GHz) system and a suitable antenna concept for advanced imaging applications. The goal is to obtain a broadband frequency response from a large target area within a short time period. Two typical approaches for the design of a free space millimetre-wave imaging setup will be discussed. The first approach consists of a focused bistatic measurement setup that includes a combination of a conical horn and a dielectric lens in order to focus the beam. The basic idea of the second approach is to use an unfocused measurement setup employing Synthetic Aperture Radar (SAR) algorithms in order to focus the image numerically. Both measurement setups will be discussed with respect to the capability for fast scanning mm-wave imaging systems. Experimental results on planar test objects demonstrate the performance of the developed W-Band system compared to a commercial vector network analyzer (VNA). © 2006 EuMA.

A Modular Vector Field Measurement System at 150 GHz, 300 GHz and 450 GHz - Hofmann, A.; Seibert, Günter; Manglberger, M.; Kalb, A.; Göbel, S.; Yao, S.; Weinzierl, Jochen; Schmidt, Lorenz-Peter; Brand, Hans (Proceedings of GeMiC, April, 2005)
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.amodul

A Vector Field Measurement System for 150 GHz - Weinzierl, Jochen; Schulz, Roland; Brand, Hans; Schmidt, Lorenz-Peter (25th International Conference on Infrared and Millimeter Waves, 2000)
The paper describes the design and realization of a heterodyne vector field measurement system. The system is designed to work in a frequency range from 148 GHz to 152 GHz with a dynamic range of about 75 dB and a phase uncertainty better than 3 degrees. It uses two channels for the measurement of the magnitude as well as the phase characteristics of an electromagnetic field. Two fundamental mixers at 150 GHz have been installed, which are both pumped by a 150 GHz phase locked solid-state oscillator unit. The system can be extended to the 300 GHz and 450 GHz frequency range by replacing these mixers by subharmonically pumped mixers. The mixers and two dielectric antennas, used as distortion minimized field probes, are mounted on a high precision 3D scanning platform. At the IF frequency of 160 MHz the vector analysis of the measured signals is done by an IF processing unit with considerably enhanced measurement accuracy by software corrections with a personal computer.
UnivIS-Import:2015-04-16:Pub.2000.tech.IE.LEH.avecto

Broadband analysis of holographic power combining circuits - Höft, Michael; Weinzierl, Jochen; Judaschke, Rolf (International Journal of Infrared and Millimeter Waves, 2002)
Holography is a promising technique for power combining applications in the frequency range of short millimeter and submillimeter waves. In this paper, quasi-optical holographic power combining circuits are investigated. An equivalent network is utilized which rigorously models horn arrays and biperiodic dielectric structures in order to design computer-generated holograms. We apply the network model to a 5-element quasi-optical power combiner and demonstrate its capability. The hologram is designed for 150GHz and has an efficiency of 92.5% with a 90% bandwidth of 5.3%. With the aid of a broadband waveguide power divider and a vector field measurement system, the circuit is analyzed.

Design and Experimental Verification of Correction Algorithms for Improving the Measurement Accuracy of a Broadband Vector IF Receiver at 160 MHz - Hofmann, A.; Kalb, A.; Manglberger, M.; Weinzierl, Jochen; Schmidt, Lorenz-Peter (Frequenz, Mai / Juni, 2005)
An Intermediate Frequency (IF) receiver unit with a center frequency of 160 MHz and a bandwidth of 80 MHz was recently developed as a core component of a novel heterodyne vector field measurement system at 150 GHz, 300 GHz and 450 GHz. The influence of different errors types on the measurement accuracy is systematically analyzed. Based on this, a strategy of enhancing the overall accuracy of the IF receiver by software algorithms was developed. Its effectiveness is verified by experimental characterization.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.design_4
Keywords: Accuracy enhancement; Correction algorithms; Iq demodulation; Thz measurements; Vector receiver

Design and Measurement of a Bandpass Filter at 300 GHz Based on a Highly Efficient Binary Grating - Biber, Stephan; Hofmann, Arnd; Schulz, R; Collischon, M; Weinzierl, Jochen; Schmidt, Lorenz-Peter (IEEE Transactions on Microwave Theory and Techniques, 2004)
A bandpass filter for 300 GHz with a stopband at 450 GHz based on a highly efficient binary grating as a frequency-selective element was developed and optimized. The geometry of the grating was carefully designed for a maximum difference angle between reflected beams at 300 and 450 GHz and for maximum efficiency at 300 GHz. The grating efficiency was optimized using a rigorous theory of diffraction, yielding a maximum efficiency of over 99.5% neglecting conductor losses. Antennas and elliptical mirrors are used for optimum quasi-optical illumination of the grating and Gaussian beam shaping. After an optimization and a comprehensive examination of the grating in an experimental heterodyne measurement setup at 300 GHz, the filter was implemented fixed tuned into a small housing with waveguide flanges. The fixed tuned setup with corrugated feed horns results in an overall flange-to-flange insertion loss of only 2.8 d
lhft_intern.bib::biber04b

Dielectric Rod Waveguide Couplers as Harmonic Filters for Millimeter and Sub-Millimeter Wave Frequencies - Hofmann, A.; Manglberger, M.; Biber, Stephan; Weinzierl, Jochen; Schmidt, Lorenz-Peter; Brand, Hans (GeMiC 2006, Karlsruhe, April, 2006)
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.LEH.dielec

Dielectric waveguides at submillimeter wavelengths - Weinzierl, Jochen; Fluhrer, C; Brand, Hans (IEEE Sixth International Conference on Terahertz Electronics, 1998)
A flexible waveguide system has been simulated using the field calculation program MAFIA, for the first time realised for frequencies up to 150 GHz and operated in two applications. The flexible waveguide system consists of a rectangular, dielectric fibre made of polyethylene combined with optimised tapers and waveguide adapters, which makes the flexible waveguide easy to use in combination with conventional waveguides. A minimum attenuation of 4 dB/m at 140 GHz; has been obtained with the dielectric waveguides, which is about 6 dB less than the measured attenuation of D-band waveguides operated at the same frequency. Additionally the phase shift of the flexible waveguides for different bending radii as well as the influence of different tapered fibre terminations was measured and is reporte
lhft_intern.bib::weinzierl98

Direction of Arrival Estimation from Secondary Surveillance RadarSignals in Presence of Hardware Imperfections - Reck, C; Berold, Ulrich; Weinzierl, Jochen; Schmidt, Lorenz-Peter (European Microwave Week / EuRAD, Amsterdam, October, 2008)
lhft_intern.bib::Reck08

End face coupling as detachable connection of dielectric waveguides at 75 GHz and 300 GHz - Weinzierl, Jochen; Schmidt, Lorenz-Peter; Hörster, Eva; et al. (Conference Digest of the 2004 Joint 29th International Conference on Infrared and Millimeter Waves and 12th International Conference on Terahertz Electronics, 2004)
End face coupling of rectangular dielectric waveguides at 75 GHz and 300 GHz is presented as a new, low-loss and powerful method for novel switching and multiplexing applications of MMW and SMMW signals. The coupling of the waveguides has been investigated, designed and optimized by extensive numerical field simulations and experimental verification at both frequencies. © 2004 IEEE.

Flexible low-loss dielectric waveguides for THz frequencies with transitions to metal waveguides - Hofmann, Arnd; Hörster, Eva; Weinzierl, Jochen; Schmidt, Lorenz-Peter; Brand, Hans (33rd European Microwave Conference, EuMC 2003, 2003)
A flexible low-loss dielectric waveguide system for sub-millimetre wave frequencies up to 600 GHz is presented, with measured attenuation values shown at 300 GHz. Mode transformers for an accurate and reproducible transition to metal waveguides have been investigated and improved. © 2003 EUMA.

Investigation of the hot embossing technology for low-cost antennas printed on polymer substrates - Kilian, Andreas; Weinzierl, Jochen; Schmidt, Lorenz-Peter (38th European Microwave Conference, EuMC 2008, 2008)
In this contribution a novel metallization technique for the realization of millimeter-wave microstrip patch antennas is presented. This technology called hot embossing is a fast and economic process originating from the production of threedimensional molded interconnect devices (3D-MID). Conductive structures are coated onto plastic parts or plastic foils using a heated stamp. To the best knowledge of the authors, this approach has not yet been employed and therefore will be investigated for the fabrication of low-cost printed antennas at millimeter-wave frequencies. The focus of this contribution is on the evaluation of process parameters and interactions with substrate and copper foil characteristics as well as the fabrication and measurement of single microstrip patch antennas designed for the 24 GHz ISM- band. Far-reaching potentials lie in the utilization of the threedimensional manufacturing technology for the construction of conformal integrated antennas. © 2008 EuMA.

MEMSTIC - Eine neue Schaltungstechnologie fuer den Submillimeter-Wellenlängenbereich - Brand, Hans; Weinzierl, Jochen (Frequenz, 2000)
lhft_intern.bib::brand00

Microwave detection of defects and inhomogeneities in low pressure injection moulded β-TCP ceramic - Martins, S.T.; Hädrich, Helmut; Dannheim, Henning; Weinzierl, Jochen; Greil, Peter; Dannheim, Henning (Advanced Engineering Materials, 2004)
The feasibility of a nondestructive microwave inspection to detect internal processing defects in low pressure injection moulded ceramic parts was investigated. A β-TCP (β-tricalcium phosphate, Ca(PO )) slurry with paraffin, ethylene vinyl acetate copolymer and stearic acid as binder system was injection moulded with a pressure of 0.2 MPa and subsequently inspected in a 94.1 GHz microwave testing device. The transmitting amplitude and phase displacement images were compared with visual inspection of the samples. The novel method was able to detect, localize and geometrically characterize inhomogeneities and non-visible defects present in green ceramic compacts.

Multistatic Short Range Ka-Band Imaging System - Gumbmann, Frank; Tran, Hue Phat; Weinzierl, Jochen; Schmidt, Lorenz-Peter (GeMIC 2009, München, March, 2009)
This paper presents the concept of a Ka-Band (26.5 - 40 GHz) multistatic active short range imaging system. The motivation for this work was the development of a fast scanning imaging system for non destructive testing (NDT) or securityscenarios. The goal was to derive a 3D reconstruction of thedevice under test (DUT). The imaging system consists of a linear receive array and spatially distributed transmitters with non focussing antenna elements. This transmit/receive array receiveris moved perpendicular to the array dimension. By switching device between each transmitter and simultaneous reception of the IDUT)scattered field by each receiver, a fast sampling of the 2D aperture plane is achieved. Due to unfocussed antenna elements Ynumerical reconstruction algorithms have to be applied for a lateral resolution. An aperture synthesis concept is presented R to reconstruct the raw data. It is based on the separation 7R-7of the reconstruction kernel into a horizontal and a vertical part. Range resolution is achieved by a broadband stepped frequency continuous wave.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.multis_1

Optimization of a fast scanning millimetre-wave short range SAR imaging system - Gumbmann, F; Tran, H; Weinzierl, Jochen; Schmidt, Lorenz-Peter (European Microwave Conference October, 2007)
This paper presents the development of a W-band short range imaging system for security and non-destructive testing applications, which uses an unfocused measurement setup employing SAR algorithms in order to focus the image numerically. The active imaging system offers the possibility to get a broadband frequency response from each pixel in the measurement plane. For real-time applications a fast scanning, monostatic virtual antenna concept has been developed and optimized. The monostatic setup is demonstrated in two different configurations, on the one hand using a quasioptical, broadband diplexer with high decoupling between transmitter and receiver channel and on the other hand a very compact setup using a commercially available high directivity waveguide coupler. The measurement setups are compared with special respect to their RF-performance. Experimental results on specific test objects are presented to prove the performance of the fast short range SAR imaging syste
lhft_intern.bib::Gumbmann07a

Permittivity Measurement Techniques at 24 GHz for Automative Polymer Composites Including Thin Films and Paint Foils - Kilian, Andreas; Weinzierl, Jochen; Schmidt, Lorenz-Peter (Proceedings of the German Microwave Conference, 2008)
Two different measurement techniques for the determination of complex permittivities of automotive polymer composites used as bumper or car body panels at 24 GHz are presented. The materials in focus of this research are basically plastics for injection molding like polycarbonate and its derivatives. The composites include thin dielectric films and paint foils for coloring and lamination of injection molded panels. The advantages and inconveniences of multi-layer measurements in rectangular waveguides and an open resonator are demonstrated. Additionally, an approach is proposed for further investigations on permittivity and loss tangent of automotive dielectrics in the millimeter-wave region.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.permit

Simulation and Measurement of Dielectric Antennas at 150 GHz - Weinzierl, Jochen; Richter, Jürgen; Rehm, Guenther; Brand, Hans (Proceedings of the 29th European Microwave Week, 1999)
Based on the development of a flexible, dielectric waveguide system for frequencies in the region of 150 GHz [1], the antenna characteristics of various tapered ends of dielectric waveguides have been studied. The flexible waveguide consists of a rectangular, dielectric fibre made of polyethylene. The paper describes the simulation and optimization of different tapers using 3D electromagnetic field computation, the precise fabrication of the antennas and the verification of the simulated data by field measurements at 150 GHz. © 1999 IEEE.
UnivIS-Import:2015-04-16:Pub.1999.tech.IE.LEH.simula

Simulation and Measurement of Dielectric Antennas at 150 GHz - Weinzierl, Jochen; Richter, J; Rehm, G; Brand, Hans (IEEE, 1999)
Based on the development of a flexible, dielectric waveguide system for frequencies in the region of 150 GHz [1], the antenna characteristics of various tapered ends of dielectric waveguides have been studied. The flexible waveguide consists of a rectangular, dielectric fibre made of polyethylene. The paper describes the simulation and optimization of different tapers using 3D electromagnetic field computation, the precise fabrication of the antennas and the verification of the simulated data by field measurements at 150 GH
lhft_intern.bib::thirty_years_LHFT_434

Spatial Resulution of Millimeter Wave Imaging at 75 - 100 GHz and 600 GHz - Tran, Hue Phat; Gumbmann, Frank; Weinzierl, Jochen; Schmidt, Lorenz-Peter (German Microwave Conference, Karlsruhe, March, 2006)
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.LEH.spatia

STIREEM - A new High Resolution Microwave Imaging Principle - Brand, Hans; Martius, Siegfried; Schmidt, Lorenz-Peter; Schür, Jan; Weinzierl, Jochen; et al. (Proceedings of the German Microwave Conference, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.stiree_8

STIREEM - A Novel Technique for High Resolution Microwave Imaging - Brand, Hans; Dexl, A.; Hagen, Johannes; Kellnberger, S.; Martius, Siegfried; Schmidt, Lorenz-Peter; Schür, Jan; Weinzierl, Jochen (Proceedings of the European Microwave Association, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.stiree

Struktur, Eigenschaften und Anwendungen dielektrischer Leitungen für Millimeterwellen - Brand, Hans; Weinzierl, Jochen (Frequenz, 2001)
lhft_intern.bib::brand01

Transmission features of frequency-selective components in the far infrared determined by terahertz time-domain spectroscopy - Winnewisser, Carsten; Lewen, Frank; Weinzierl, Jochen; Helm, Hans (Applied Optics, 1999)
The transmission features in the far infrared region of dichroic high-pass filters and a cross-shaped bandpass filters are studied using an electro-optic sampling terahertz time-domain spectrometer. The frequency-selective components (FSC) transmission experiments show good agreement with the transmission theories, showing that they can be applied for a priori filter design.

Vector Field Measurements at 150 GHz - Weinzierl, Jochen; Brand, Hans; Schmidt, Lorenz-Peter (Proceedings of the 11th Conference and Exhibition on Microwaves, Radio Communication and Electromagnetic Compatibility MIOP 2001, 2001)
UnivIS-Import:2015-04-16:Pub.2001.tech.IE.LEH.vector